Evaluation of the severity of malocclusions in children affected by osteogenesis imperfecta with the peer assessment rating and discrepancy indexes - Rizkallah, Jean; Schwartz, Stephane; Rauch, Frank; Glorieux, Francis; Vu, Duy-Dat; Muller, Katia; Retrouvey, Jean-Marc (American journal of orthodontics and dentofacial orthopedics, 2013)
Osteogenesis imperfecta is a heritable disorder affecting bone and tooth development. Malocclusion is frequent in those affected by osteogenesis imperfecta, but this has not been studied in detail. The purpose of this study was to describe and quantify the severity of malocclusions in patients with osteogenesis imperfecta. Articulated dental casts were obtained from 49 patients diagnosed with osteogenesis imperfecta (ages 5-19 years; 28 female) and 49 age- and sex-matched control subjects who did not have osteogenesis imperfecta. Both groups were seeking orthodontic treatment. Malocclusions were scored by using the peer assessment rating (PAR) and the discrepancy index (DI). The average United Kingdom weighted PAR scores were 31.1 (SD, 14.5) for the osteogenesis imperfecta group and 22.7 (SD, 10.7) for the control group (P <0.05). The mean United States weighted PAR scores were 32.2 (SD, 15.0) for patients with osteogenesis imperfecta and 21.6 (SD, 9.6) for the controls (P <0.05). The average modified DI scores were 29.8 (SD, 20.2) for the osteogenesis imperfecta group and 12.4 (SD, 6.8) for the control group (P <0.05). Group differences were greatest for lateral open bite (osteogenesis imperfecta group, 7.1; control group, 0.3) for the DI parameters and anterior crossbite (osteogenesis imperfecta group, 13.0; control group, 3.8 [United Kingdom]) for the PAR. Both the PAR and the DI showed that malocclusions were significantly more severe in patients with osteogenesis imperfecta than in the control group. There was a higher incidence of Class III malocclusion associated with anterior and lateral open bites in patients affected by osteogenesis imperfecta.